Computerised separate source voltage test for low power transformer using solid state devices / Abdul Manan Abdul Aziz - Abdul Aziz, Abdul Manan (1995)
This project presents a computer based transformer testing for separate source voltage test. Separate source voltage test is a routine test required by Technical Committee i.e BSI, EC for every transformer before despatch, to ensure that it is in accordance with the specification. The reason for computer based is aimed to automate data collections for the transformer under testing . Most of the conventional testing is been done manually and the data taken are by observation. Hence this project offer an alternative design to data acquisition, control and monitor the system. The proposed project is consists of a tranduser system to read supply current, supply voltage and voltage on the transformer under testing. An interface card that digitized the waveforms and provides interface with the computer. The software written in C language uses available hardware to calculate and control the whole system The system reads the supply voltage, supply current and voltage on the transformer under testing, then the system will read the voltage on the transformer under testing every two seconds until one minute. The project has advantages like flexibility in programming and ease of use.